Validitas Perangkat Pembelajaran Fisika Flipped Classroom Learning Cycle 5E Inquiry Berorientasi HOTS - Dens E. S. I. Asbanu; Landiana Laos (Universitas Nurul Huda, 2023)
This research aims to produce valid and reliable flipped classroom learning cycle 5E Inquiry physics learning devices that are suitable for use in learning. The research method is quantitative. The research subjects were learning tools, namely lesson plans, worksheets, and test instruments. The learning device validators consist of five people from expert elements of physics lecturers and teachers as practitioners. Data collection techniques used validation questionnaires. The data analysis technique used descriptive quantitative with the Aiken formula and percentage of agreement. The learning device is declared valid if the value of V aspects assessed is > 0.80 on the criteria of high validity and is reliable with a percentage of agreement > 75%. The results showed that the lesson plans, worksheets, and test instruments with a validity value of > 0.80 and a percentage of agreement > 75% meant they were reliable. Thus, it is concluded that the learning tools are valid and reliable so that they are suitable for use in learning. It is suggested that this learning tool can be used as an alternative solution to increase the HOTS of junior high school students.